SMART SEAL BASE ON WIFI USING WEB SERVICE PHP - Irawati Dewi Syahwir; Suprijanto Suprijanto; Gayuh Tentri; Rayhan Putra Pratama (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Technological developments, especially in the IoT (Internet of Things), play a significant role in various fields. In addition to achieving a modern and efficient work environment, IoT can also play a role in the security sector, which has now become a significant need. One of the roles of IoT in the security sector is that it can be applied to calibrated TMWE (Measuring, Dosing, Weighing, and Equipment). So that it can guarantee the correctness of the measurement results from the TMWE, continuous monitoring can be carried out so that fraud does not occur. One of the innovations in this regard is the smart seal. The use of smart seals is prioritized for fixed TMWE, which is vulnerable to theft and breaches. This system is designed based on IoT, which is integrated with cloud services and GPS systems that allow the use of web-based applications for online monitoring of seal conditions by users. Data from the seal will be sent to the server via wifi network and stored in a database, to be displayed in web service with a user, admin, and signer access. In addition to providing information to users about the seal’s location, the use of the GPS also aims to make it easier for admins to detect the seal’s location in the event of a violation.